2020
DOI: 10.1002/isd2.12148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating integrated use of information technologies in secondary schools of Ethiopia using design‐reality gap analysis: A school‐level study

Abstract: The purpose of this study was to examine the level of readiness of Ethiopian secondary education systems in terms of access to technologies and preparedness in skills and motivation for the integrated use of information communication technologies (ICT) for quality education. To serve this end, a Design‐Reality Gap Analysis approach was employed. Relevant data were collected from teachers, students, and school leaders through a questionnaire survey, and the result was cross‐examined against the national goals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…According to Bati et al (2021), first of all one's work is done with access to technologies for the integrated use of information technologies for quality education, skills and motivation. In terms of the level of readiness, the secondary education system in Ethiopia aims to examine student learning and as a result for better use of information technology in in-school and out-of-information technology resources and services they concluded that they revealed the importance of an integrated strategy.…”
Section: Related Studiesmentioning
confidence: 99%
“…According to Bati et al (2021), first of all one's work is done with access to technologies for the integrated use of information technologies for quality education, skills and motivation. In terms of the level of readiness, the secondary education system in Ethiopia aims to examine student learning and as a result for better use of information technology in in-school and out-of-information technology resources and services they concluded that they revealed the importance of an integrated strategy.…”
Section: Related Studiesmentioning
confidence: 99%
“…Policymakers should focus on improving the learning resources available to rural schools across the region, especially in response to a lack of technological resources they are to develop students' digital competencies (Bati & Workneh, 2021;Josic et.al., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mengevaluasi secara sosial dan teknis tantangan digitalisasi layanan penyuluhan pertanian di Ethiopia (Atinaf et al, 2020). Menguji tingkat kesiapan sistem pendidikan menengah Ethiopia yang terintegrasi teknologi komunikasi informasi (TIK) untuk pendidikan berkualitas (Bati & Workneh, 2021).…”
Section: Pendahuluanunclassified